2019
DOI: 10.1073/pnas.1818553116
|View full text |Cite
|
Sign up to set email alerts
|

Nontoxic nanopore electroporation for effective intracellular delivery of biological macromolecules

Abstract: We present a simple nanopore-electroporation (NanoEP) platform for delivery of nucleic acids, functional protein, and Cas9 single-guide RNA ribonucleoproteins into both adherent and suspension cells with up to 80% delivery efficiency and >95% cell viability. Low-voltage electric pulses permeabilize a small area of cell membrane as a cell comes into close contact with the nanopores. The biomolecule cargo is then electrophoretically drawn into the cells through the nanopores. In addition to high-performance d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
171
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(186 citation statements)
references
References 32 publications
4
171
3
Order By: Relevance
“…A > 95 % electrotransfection rate was achieved with the optimized pulsing condition. Even the rate of transient expression of reporter genes as well as the cell viability using the OptiMEM-GlutaMAX in the current study were as high as that of newly reported mechanical-electrical (7) and nanopore-electrical approaches (12). We used plasmids with various sizes, from 6.2 to 13.5 kb, and found a high transfection rate and cell viability irrespective of the plasmid size.…”
Section: Discussionmentioning
confidence: 48%
“…A > 95 % electrotransfection rate was achieved with the optimized pulsing condition. Even the rate of transient expression of reporter genes as well as the cell viability using the OptiMEM-GlutaMAX in the current study were as high as that of newly reported mechanical-electrical (7) and nanopore-electrical approaches (12). We used plasmids with various sizes, from 6.2 to 13.5 kb, and found a high transfection rate and cell viability irrespective of the plasmid size.…”
Section: Discussionmentioning
confidence: 48%
“…Using electric pulses, cell membranes can be transiently perforated so that a large variety of materials can be intracellularly delivered. In recent years, electroporation coupled with micro/nanostructures, [ 151–154 ] called as micro/nanoscale electroporation (MEP/NEP), has significantly improved cell viability while ensuring efficient transfection. These micro/nanostructure‐mediated local electric fields can more gently penetrate the cell membrane, and the resulting cell damage can be almost negligible.…”
Section: Assisted Penetrationmentioning
confidence: 99%
“…This allows the application of lower voltage without reducing the electric field strength. This approach minimizes heating and pH changes [55,56]; as a consequence cell viability after electroporation and transfection efficiency are both increased [57][58][59][60][61][62].…”
Section: Bulk and Localized Electroporationmentioning
confidence: 99%
“…In the nanopore-electroporation (NanoEP) platform cells are deposited onto a polycarbonate membrane that it contains 100 nm diameter nanopores with density of 0.2 pores per mm 2 . The pores are connected to a liquid reservoir and cargoes can then be delivered into numerous cells via localized electroporation after establishing an electric field [58]. NanoEP has been used to deliver a variety of cargoes, including mRNAs, DNA plasmids, CRISPR/Cas9 RNA-protein complexes and functional stromal interaction molecule 1 (STIM1) proteins into the cell cytoplasm [58].…”
Section: Bulk and Localized Electroporationmentioning
confidence: 99%
See 1 more Smart Citation